RF CMOS modeling： a novel empirical large-signal model for an RF-MOSFET - 孙玲玲 吕彬义 刘军 陈磊 (Journal of semiconductors, 2010)
A novel empirical model for large-signal modeling of an RF-MOSFET is proposed. The proposed model is validated in the DC, AC, small-signal and large-signal characteristics of a 32-finger nMOSFET fabricated in SMIC＇s 0.18 μm RF CMOS technology. The power dissipation caused by self-heating is described. Excellent agreement is achieved between simulation and measurement for DC, S-parameters （50 MHz-40 GHz）, and power characteristics, which shows that our model is accurate and reliable.